Paul's gift from Philippi conventions of gift-exchange and Christian giving - Peterman, Gerald W. (Cambridge, U.K. Cambridge U.P., 1997)
Includes bibliographical references and indexes
Revision of thesis (Ph.D) - Kings College, 1992
Keywords: Bible. N.T. Philippians IV : 10-20 -- criticism, interpretation, etc; Christian giving -- Biblical teaching; Rome -- social life and customs